The Role of Adjuvant Treatment in Craniofacial Malignancy: A Critical Review - König, Marton; Osnes, Terje; Bruland, Øyvind; Sundby Hall, Kirsten; Bratland, Åse; Meling, Torstein R. (Frontiers in Oncology, 2020)
Background Tumors originating from the craniofacial region usually present in a locally advanced stage with frequent involvement of adjacent sites and have a strong tendency for local recurrence in the absence of adjuvant therapy, even when the original surgical resection was presumed to be radical. In the past decades, several advances in the radiological diagnosis and treatment of craniofacial malignancies have been introduced, there are, however, no randomized trials that define the optimal multimodal treatment of these tumors because of their rarity as well as heterogeneity in both histology and site of origin. The aim of this study was to conduct a critical review of the role of adjuvant therapy in the treatment of craniofacial malignancy. Method We conducted a critical review of the past and contemporary literature available, focusing on adjuvant oncological treatments of the most common craniofacial malignancies. Results Preoperative radiotherapy can have a documented role in the treatment of olfactory neuroblastoma and soft tissue sarcoma, while preoperative chemotherapy can be advocated in the treatment of sinonasal undifferentiated carcinoma, neuroendocrine carcinoma, olfactory neuroblastoma, and craniofacial sarcoma (both soft-tissue and high-grade osteosarcoma). Postoperative radiotherapy has a well-established role in the treatment of most craniofacial malignancies, apart from mucosal melanoma. The role of postoperative chemotherapy is unclear in most histologies, but is commonly used during the treatment of well selected cases of paranasal sinus carcinoma, olfactory neuroblastoma, mucosal melanoma, soft tissue sarcoma and high-grade craniofacial osteosarcoma. Discussion Alongside developments in surgery, there have also been improvements in diagnostics, radiotherapy, and chemotherapy. Implementation of novel radiation techniques allows delivery of higher radiation doses while minimizing irradiation-related morbidity. Better understanding of tumor biology allows the construction of more complex treatment strategies, incorporating adjuvant chemotherapy either pre- or postoperatively. In the era of personalized targeted therapy, rapid strides are being made to identify specific tumor-targets for use of novel biologic agents, with the potential to change current management paradigms.